The Evaluation of Effectiveness of Commercial Banks Participating In M&A In Vietnam - Doan Thi Lien (Genius Publishing Group, 2022)
Mergers and acquisitions (M&A) are seen as the principle ”mechanisms” that are intended in the corporate world to achieve the increasing importance and attention especially with the advent of intense globalization. This is evident from the magnitude and growth of deal values and resultant ‘mega-mergers’ transacted in recent times. This research work attempts to assess the implication of merger and acquisition of commercial banks in Vietnam on their profitability and other associated measures of performance. The result of the analysis revealed that there is significant relationship between pre and post merger/acquisition capital base of commercial banks and level of profitability, there is significant difference between pre and post-merger acquisition earnings per shares. Merger/acquisition have also increased the capitalization of commercial banks with evidences of changes in company’s share ownership, increase in the cost of services and changes in bank lending rates. Based on these findings, it can be concluded that the merger and acquisition of programmed has improved the overall performances of banks significantly and also has contributed immensely to the growth of the real sector for sustainable development. The banking industry is currently experiencing the most significant merger movement in its history. There has been a quantum jump in the number of mergers and acquisitions in the past few years. The increase in the number of mergers is even more significant because the average size of each transaction is also increasing. The consequence of these two trends is that in 1983 alone, over $40 billion in assets were acquired within the commercial banking merger activity.
Keywords: capitalization; profitability; Vietnam; banking industry